Dispute Resolution Of "Supreme" Brand Rights: (Study of Review Decision Number 37 Pk/Pdt. Sus-Hki/2023) - Kartiko, Nafis Dwi; Soegiono, Samuel Putra; Rohman, Mohammad Syafi'ur; Tedjokusumo, Dave David; Siswanto, Carissa Amanda (Jurnal Hukum dan Sosial Politik, 2024)
In an era of globalization that has a significant impact on industry and commerce, trademark rights disputes are a crucial issue that needs serious attention. One trademark rights dispute that has attracted attention is the case of "Supreme," which is the focus of this study by detailing the Review Decision Number 37 PK/PDT. SUS-HKI/2023. This dispute involves companies with the trademark "Supreme," and its resolution has an important impact on trademark law in Indonesia. This research aims to dig deeper into the resolution of trademark rights disputes through these case studies. Analysis of court decisions, judges' considerations, and the legal basis used will provide a more comprehensive understanding of the trademark dispute resolution mechanism in Indonesia. Through this search, it is expected to find significant contributions to the development of trademark rights regulations and dispute resolution at the national level. This research uses normative juridical method with statutes approach, conceptual approach and case approach. The result of this research is that the trademark dispute resolution process in Indonesia follows predetermined legal steps, starting from filing a lawsuit in the District Court, continuing with the cassation process in the Supreme Court, and can reach the review stage in the Supreme Court if necessary. This approach reflects Indonesia's seriousness in handling brand disputes fairly and efficiently. The study also emphasizes the importance of good faith in the trademark registration process.